DEVELOPING SOCIAL INCLUSION AND 21ST CENTURY SKILLS THROUGH PROJECT BASED LEARNING IN THE ERASMUS + PROJECT "WISH" - Darius Borovic (National Centre for Policy and Evaluation in Education, 2019)
The study presents the findings of an experimental research related to the implementation of Project Based Learning in the Erasmus Plus KA201 project Work for an Inclusive School Heritage in Romanian high-schools. One of the projects goals was to develop, to apply and to exchange innovative practices in the 5 countries of the Erasmus partnership (Slovakia, Turkey, Catalonia - Spain, Italy and Romania). The experimental research studied an original Project Based Learning strategy developed from John Dewey's ideas, Project Citizen and the MAPA methodology for planning funding projects. Teachers from the 5 partner countries were trained and the students from the participant high-schools planned and implemented several social action projects. In Romania we surveyed a sample of 226 students using a validated questionnaire with the majority of questions taken from international literature. The quasi-experimental research proves a statistically significant increase of the students' positive attitudes toward migrants and minorities, several institutions, civic action, and social inclusion. The desire to participate in solving problems of the community and the level of development of several 21st Century Skills have also improved.